TEORI TA‘AQQULÎ DAN TA‘ABBUDÎ MENURUT FIQH JINAYAH DAN APLIKASINYA DALAM PENERAPAN SANKSI PIDANA KORUPSI - Nasrullah Nasrullah (Asy-Syari'ah, 2014)
One of definitions of the corruption is the misuse of power, abuse of power, or the misuse of public position for personal gain. Corruption is part of “extraordinary crime”, which is the act which destroys the economic, social, and the eradication should be done with the priority scale. The penalty or sanction against corruption actors should be done firmly, strongly, and emphatically that makes deterrent effect. In Islam, one of the approaches for the application of penalty in Islamic Criminal Law can be done theoretically with ta‘abbudî and ta‘aqqulî approach. Therefore, this paper will explain the theory of ta‘aqqulî and ta‘abbudî according to Islamic Criminal Law perspective and its application to the corruption actors.